Event management education and the meeting and business event competency standards: the perspective from alumni - Gamble, Tia' R. (Kansas State University, 2019)
Throughout the last two decades, the meeting and events community has taken deliberate steps to establish itself as an ever-growing industry and economic powerhouse. To assist in these efforts, the Meeting Professionals International (MPI) Association spearheaded a collective effort among industry groups to create a list of competencies designed to facilitate professionals and educators becoming globally successful in various areas of the industry. The Meeting and Business Event Competency Standards (MBECS) were developed and consist of 12 overarching standards, 33 sub-categories, 134 specific competencies, and an in-depth curriculum for educators. This exploratory research investigated the perspectives of event professionals who graduated between December 2016 and 2018 about their educational preparation, based on the MBECS competencies. The research also explored whether the number of event courses taken, the academic unit offering the event courses and mandatory work-based courses influenced the event professionals’ preparation for their current positions. Since there is limited research on event management education, this research contributes to the literature on the subject. Respondents’ perceptions of their formal event management education were compared with the MBECS and educational variables to determine skills that could benefit from enhancement in event management education. Several analyses were conducted to address research questions: 1. How do event professionals self-evaluate their level of educational preparedness using the globally accepted MBECS competencies? 2. Is there any difference of the level of educational preparedness reported based on specifics of curriculum (academic unit offering event courses, number of taken event courses taken, and required work-based courses)? First, a descriptive analysis approach was taken to summarize the population’s demographic and educational features to address research question one concerning event professionals’ self-perception of educational preparedness based on the 33 globally accepted MBECS skills. Second, a Principal Component Analysis was used to group the 33 MBECS into four components. Finally, all questions related to MBECS skill components and education were analyzed through one-way ANOVA to determine differences across education variables and event professionals’ self-perception of educational preparedness based on the four MBECS components. The findings provided a socio-demographic and educational profile of entry-level event professionals who completed a bachelor’s degree with an emphasis in event management between 2016 and 2018. This research found communication, professionalism, and administrative were the skills for which the entry-level professionals perceived they were most prepared. Engaging speaker/performers, managing human resource plans, and technical production were the three competencies rated the lowest based on their formal event management education. This study’s findings loaded 23 of the 33 MBECS sub-skills into four components; planning, coordinating, strategic management, and marketing. Five statically significant differences were identified among twelve items within the three educational variables of number of event courses taken, academic unit offering the event courses and mandatory work-based courses. Three of the five statistically significant different components found violated the assumption of homogeneity. This study discussed these relationships, implications, and limitations, and presented suggestions for future research.
Keywords: event management; higher education; competency; trends; profession; curriculum; college